One-step isolation of sappanol and brazilin from Caesalpinia sappan and their effects on oxidative stress-induced retinal death - Uddin, Golam Mezbah; Kim, Chul Young; Chung, Donghwa; Kim, Kyung-A; Jung, Sang Hoon (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2015)
Caesalpinia sappan is a well-distributed plant that is cultivated in Southeast Asia, Africa, and the Americas. C. sappan has been used in Asian folk medicine and its extract has been shown to have pharmacological effects. Two homoisoflavonoids, sappanol and brazilin, were isolated from C. sappan by using centrifugal partition chromatography (CPC), and tested for protective effects against retinal cell death. The isolated homoisoflavonoids produced approximately 20-fold inhibition of N-retinylidene-N-retinyl-ethanolamine (A2E) photooxidation in a dose-dependent manner. Of the 2 compounds, brazilin showed better inhibition (197.93 +/- 1.59 mu M of IC50). Cell viability tests and PI/Hoechst 33342 double staining method indicated that compared to the negative control, sappanol significantly attenuated H2O2-induced retinal death. The compounds significantly blunted the up-regulation of intracellular reactive oxygen species (ROS), and sappanol inhibited lipid peroxidation in a concentration-dependent manner. Thus, both compounds represent potential antioxidant treatments for retinal diseases.
Keywords: GANGLION-CELL DEATH; BLUE-LIGHT; ANTIOXIDANT; GLAUCOMA; INSULTS; DAMAGE; LINE